Phosphorylation of bamboo mosaic virus satellite RNA (satBaMV)-encoded protein P20 downregulates the formation of satBaMV-P20 ribonucleoprotein complex - Vijayapalani, Paramasivan; Chen, Jeff Chien-Fu; Liou, Ming-Ru; Chen, Hsin-Chuan; Hsu, Yau-Heiu; Lin, Na-Sheng (Nucleic acids research, 2012)
Bamboo mosaic virus (BaMV) satellite RNA (satBaMV) depends on BaMV for its replication and encapsidation. SatBaMV-encoded P20 protein is an RNA-binding protein that facilitates satBaMV systemic movement in co-infected plants. Here, we examined phosphorylation of P20 and its regulatory functions. Recombinant P20 (rP20) was phosphorylated by host cellular kinase(s) in vitro, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and mutational analyses revealed Ser-11 as the phosphorylation site. The phosphor-mimic rP20 protein interactions with satBaMV-translated mutant P20 were affected. In overlay assay, the Asp mutation at S11 (S11D) completely abolished the self-interaction of rP20 and significantly inhibited the interaction with both the WT and S11A rP20. In chemical cross-linking assays, S11D failed to oligomerize. Electrophoretic mobility shift assay and subsequent Hill transformation analysis revealed a low affinity of the phospho-mimicking rP20 for satBaMV RNA. Substantial modulation of satBaMV RNA conformation upon interaction with nonphospho-mimic rP20 in circular dichroism analysis indicated formation of stable satBaMV ribonucleoprotein complexes. The dissimilar satBaMV translation regulation of the nonphospho- and phospho-mimic rP20 suggests that phosphorylation of P20 in the ribonucleoprotein complex converts the translation-incompetent satBaMV RNA to messenger RNA. The phospho-deficient or phospho-mimicking P20 mutant of satBaMV delayed the systemic spread of satBaMV in co-infected Nicotiana benthamiana with BaMV. Thus, satBaMV likely regulates the formation of satBaMV RNP complex during co-infection in planta.